Noise monitoring using mobile phones - Thadeus, Claudio (2014)
Nowadays, almost every person in the world owns a smartphone. A person would carry his smartphone wherever he goes. This gives a chance to collect some information from the location using some of the sensors embedded in the smartphone. The information that this project is focused on gathering is sound.